A Comparative Study Between the Commercial Banks Sector in Egypt and the UK: A Case Study on the Performance of the National Bank of Egypt (NBE) and Barclays Bank- UK - Hassanien, Dr. Karim Badr El-Din Attia (IJRDO - Journal of Business Management, 2018)
This research paper is designed to explore the factors affecting the commercial banks financial performance in Egypt versus the UK. These comparisons cover wide span including the client’s deposits, the risks in the covered sectors, the application of the Basel requirements, the Fitch rating, and the surrounding environment. The Egyptian banking sector and the European banking sector are two very successful banking sectors worldwide. The Egyptian banking sector isn’t only one of the largest banking sectors in North Africa, but also it is one of the most profitable one. In the 2000s, Egyptian lenders have gained easily from the high-yielding government debt after the 2011 revolution. On the other hand, the European banking sector targeted sustained economic expansion over the past years and the banking sector supported the financial stability within the Euro zone especially after the financial difficulties in some member countries, such as Greece. The European banking profitability has increased after the introduction of untraditional monetary policy measures. On the other hand, the sources of the weakness can be divided into cyclical factors, cost inefficiencies, and external competitive challenges emerging from outside the banking sector. This study is based on a comparative case study of the biggest bank in terms of total assets in Egypt and the UK. The two banks that were qualified to meet this requirement were the National Bank of Egypt (NBE) in Egypt, and Barclays Bank in the UK. It was found at one stage of the comparative analysis that there is a significant effect of both the clients’ risk and clients’ deposits on the financial performance of the banks on both countries.